Strategi Pemasaran dalam Pengembangan Pelayanan Klinik Estetika - Daruki, Maria Wahyu; Suwedia, I Nyoman Gede Bayu Wiratama (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
Aesthetic Services is growing in many big cities and developing cities in Indonesia. It is due to the tendency of people who want to improve their physical performance, in the era of national health insurance, private hospitals must also improve and add services to clients while maintaining good service and adding new services which can be another source of income for hospital. Services provided with mottto from Bhakti Rahayu Hospital Denpasar "we care and we serve" Bhakti Rahayu Hospital Denpasar wants to be able to provide beauty and skin care services to the community at large with low prices and remain competitive so marketing becomes an important thing in order to develop and continue to grow. This study shows the importance of marketing strategies in the growth of aesthetic services. This study uses a qualitative descriptive study with in-depth interviews with stakeholders related to the development of aesthetic services at Bhakti Rahayu Hospital in Denpasar.